PENGARUH MOTIVASI KERJA, KOMPENSASI DAN PENGEMBANGAN KARIR KARYAWAN TERHADAP KEPUASAN KERJA KARYAWAN - Iermawati, Etty Yanis (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2021)
This study aims to determine the effects of work motivation, compensation and employee career development on employee job satisfaction Data analysis using Multiple Linear Regression. From result of data processing got variable (1) work motivation have positive and significant effect to employee job satisfaction. From the results of correlation matrix between dimensions can be seen that the most powerful work motivation variable is the dimension of the need for achievement of the work dimension itself on job satisfaction variable. (2) Compensation has no effect on employee job satisfaction. (3) Career development has a positive and significant impact on employee job satisfaction. From the results of correlation matrix between dimensions can be seen that the most powerful career development variables are from the dimensions of career management to the dimensions of salary and promotion (4) Work motivation and career development employees simultaneously affect employee job satisfaction.